Integrating national and international research, and exploringcountry-specific factors contributing to work addiction; Commentaryto "Workaholism – psychological and social determinants of workaddiction" - Atroszko, Paweł Andrzej; Atroszko, Bartosz (Current Problems of Psychiatry, 2025)
The recent paper by Soroka et al. in Current Problems of Psychiatry constitutes a review of workaholism literature [1]. The review includes the majority of Polish sources (18/23; 78%), which is an important and appreciated effort to summarize some of the significant findings present in the Polish language literature on work addiction. However, there are crucial issues related to the Authors' statements concerning the status of work addiction research that should be addressed. Firstly, the paper is purported to constitute a review of work addiction/workaholism literature, not Polish language literature on the issue. Secondly, the Authors wrote that "Workaholism as a psychological and social phenomenon is the object of only a few empirical studies" (p. 7). ...